Approach to the management of pregnancy in patients with pseudoxanthoma elasticum: a review. (16th November 2016) - Camacho, Marta; Rengel, Cristobal; López-Herrero, Elisa; Carrillo, Juan L.; Eslava, Agustín J.; Valdivielso, Pedro
Abstract: Management of pregnancy in patients with rare diseases is often guided by incomplete knowledge because of a lack of high-quality case control studies or single-centre experience. Pseudoxanthoma elasticum (PXE) is an autosomal recessive metabolic disorder that results in calcification of elastic fibres of the skin, retina, and arteries, leading to skin lesions, eventual central visual loss, and potential arterial insufficiency in most patients. It is due to mutations in ABCC6, which encodes the eponymous membrane transport protein. We review the literature on pregnancy in PXE, including the effects of the diseases on pregnancy and its complications, the effect of PXE on the foetus, and the effects of pregnancy on PXE, and conclude that in the majority of pregnancies in women with PXE, the outcome for mother, baby, and the disease is uneventful. We also provide recommendations for managing pregnancy in PXE.